Single- and double-stranded DNA binding proteins act in concert to conserve a telomeric DNA core sequence - Rhodin Edsö, Jenny (BioMed Central, 2011)
BACKGROUND: Telomeres are protective cap structures at the ends of the linear eukaryotic chromosomes, which provide stability to the genome by shielding from degradation and chromosome fusions. The cap consists of telomere-specific proteins binding to the respective single- and double-stranded parts of the telomeric sequence. In addition to the nucleation of the chromatin structure the telomere-binding proteins are involved in the regulation of the telomere length. However, the telomeric sequences are highly diverged among yeast species. During the evolution this high rate of divergency presents a challenge for the sequence recognition of the telomere-binding proteins. RESULTS: We found that the Saccharomyces castellii protein Rap1, a negative regulator of telomere length, binds a 12-mer minimal binding site (MBS) within the double-stranded telomeric DNA. The sequence specificity is dependent on the interaction with two 5 nucleotide motifs, having a 6 nucleotide centre-to-centre spacing. The isolated DNA-binding domain binds the same MBS and retains the same motif binding characteristics as the full-length Rap1 protein. However, it shows some deviations in the degree of sequence-specific dependence in some nucleotide positions. Intriguingly, the positions of most importance for the sequence-specific binding of the full-length Rap1 protein coincide with 3 of the 4 nucleotides utilized by the 3' overhang binding protein Cdc13. These nucleotides are very well conserved within the otherwise highly divergent telomeric sequences of yeasts. CONCLUSIONS: Rap1 and Cdc13 are two very distinct types of DNA-binding proteins with highly separate functions. They interact with the double-stranded vs. the single-stranded telomeric DNA via significantly different types of DNA-binding domain structures. However, we show that they are dependent on coinciding nucleotide positions for their sequence-specific binding to telomeric sequences. Thus, we conclude that during the molecular evolution they act together to preserve a core sequence of the telomeric DNA.